2017
DOI: 10.1111/wvn.12238
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Psychosocial Interventions for People With Spinal Cord Injury During Inpatient Rehabilitation: Implications for Evidence‐Based Practice

Abstract: This review found promising evidence that approaches to psychosocial care for people with SCI can improve their cognitive appraisal and psychosocial adaptation. Significant methodological limitations weakened study findings. Additionally, because studies were conducted in only a few developed countries with subgroups of patients having specific illness characteristics or severity, their generalizability to the wider SCI population is uncertain. Therefore, future research should adopt more robust study designs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…However, this review focused on a range of mostly physical interventions, including electrical brain stimulation, exercise, acupuncture, hypnosis, transcutaneous electrical nerve stimulation (TENS) and included only one trial of CBT. Further systematic review evidence has evaluated psychosocial interventions for inpatients with SCI, concluding that more work is required to evidence such interventions for this group [8]. Whilst the efficacy of CBT has been systematically reviewed [9,10], the rapidly growing research interest and evidence surrounding mindfulness-based interventions has not been reviewed systematically, despite the fact that such a review could provide valuable guidance on the future study and application of mindfulness for people with SCI.…”
Section: Introductionmentioning
confidence: 99%
“…However, this review focused on a range of mostly physical interventions, including electrical brain stimulation, exercise, acupuncture, hypnosis, transcutaneous electrical nerve stimulation (TENS) and included only one trial of CBT. Further systematic review evidence has evaluated psychosocial interventions for inpatients with SCI, concluding that more work is required to evidence such interventions for this group [8]. Whilst the efficacy of CBT has been systematically reviewed [9,10], the rapidly growing research interest and evidence surrounding mindfulness-based interventions has not been reviewed systematically, despite the fact that such a review could provide valuable guidance on the future study and application of mindfulness for people with SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive coping as a significant predictor of self‐efficacy could be an underlying mechanism for coping‐based interventions in enhancing people’s psychosocial adaptations to SCI. People’s coping abilities post‐SCI or in relation to other chronic disabilities can be enhanced by various psychosocial interventions including emotion management (e.g., relaxation, mindfulness‐based interventions), challenging negative thoughts, and positive behavioral reinforcement (Anson & Ponsford, 2006; Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A few previous studies have investigated self‐efficacy levels in the SCI population (Bhattarai, Jin, Smedema, Cadel, & Baniya, 2021; Craig, Tran, Guest, & Middleton, 2019; van Diemen et al, 2017), and findings indicated lower self‐efficacy levels than those in the general population (Craig et al, 2019; Middleton, Tran, & Craig, 2007). The self‐efficacy scores (as measured using the Moorong Self‐Efficacy Scale [MSES]) of Chinese people with SCI (Li, Bressington & Chien, 2019; self‐efficacy scores ranged from 50 to 60) may also be lower than those seen in SCI patients in other countries (e.g., Australia; Craig et al, 2019; self‐efficacy scores ranged from 60 to 100; Li, Bressington, & Chien, 2017). Chinese people with SCI may face additional challenges and difficulties because the infrastructure and community support systems are less developed than those in developed Western countries (Zhang, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Outcomes of isolation include high anger and frustration [14,27,28] anxiety and depression [29][30][31] and reduced quality of life [32]. Research demonstrates that infection-isolation results in longer length of overall inpatient stay [33,34] and rehabilitation can be further limited by pragmatic factors, such as restricted access to group-based psychoeducation, a crucial component impacting rehabilitation [35,36]. Thus, strict contact precautions imposed on patients with MRSA can have potentially detrimental physical and psychosocial impacts on health and rehabilitation, compounded by severe stigmatisation and reduced patient autonomy [28,37].…”
Section: Introductionmentioning
confidence: 99%